The unquiet frontier rising rivals, vulnerable allies, and the crisis of American power - Grygiel, Jakub J.; Mitchell, A. Wess (Princeton University Press, 2016)
The Unquiet Frontier explains why the United States needs a new grand strategy that uses strong frontier alliance networks to raise the costs of military aggression in the new century. Jakub Grygiel and Wess Mitchell describe the aggressive methods rival nations are using to test U.S. power in strategically critical regions throughout the world.